Bias and judicial narrative: a critical discourse analysis of the ECtHR and ECJ case law on religious symbols - Mauro Gatti; Giulia Evolvi (European Law Open)
The use of religious symbols has sparked heated debate and numerous judicial cases across Europe. Early case law from the European Court of Human Rights (ECtHR) has been criticised for allegedly employing biased discourses. However, it remains unclear whether such biased discourses are present in recent ECtHR rulings or in comparable decisions by the European Court of Justice (ECJ). This article applies Critical Discourse Analysis, a linguistic and social science approach, to examine the narratives used by the ECtHR and ECJ in cases involving religious symbols. It argues that religious and gender biases are pervasive in ECtHR judgements. While the ECJ generally employs neutral language, biased discourses occasionally emerge in the ‘subtext’ of its decisions. These biases are not incidental but serve as strategic tools within judicial narratives, reinforcing the argumentative legitimacy of rulings for audiences influenced by societal prejudices.